2014
DOI: 10.2527/jas.2013-6630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental vitamin D3 on serum 25-hydroxycholecalciferol and growth of preweaning and nursery pigs1,2

Abstract: Four experiments were conducted to investigate the effects of varying concentrations of supplemental vitamin D3 on pig growth, feed preference, serum 25-hydroxycholecalciferol [25(OH)D3] , and bone mineralization of nursing and weanling pigs. In Exp. 1, 270 pigs (1.71 ± 0.01 kg BW) were administered 1 of 3 oral vitamin D3 dosages (none, 40,000, or 80,000 IU vitamin D3) on d 1 or 2 of age. Increasing oral vitamin D3 increased serum 25(OH)D3 on d 10 and 20 (quadratic, P < 0.01) and d 30 (linear, P < 0.01). No di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
8
11
0
1
Order By: Relevance
“…These results again agree with some recent research (Flohr et al, 2014a). Rortvedt et al (2012) also reported no improvement of ADG for 35 d after weaning in pigs administered a single oral mega-dose of vitamin D 3 (40,000 IU) at birth (0.38 kg/d) compared with control pigs (0.41 kg/d).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…These results again agree with some recent research (Flohr et al, 2014a). Rortvedt et al (2012) also reported no improvement of ADG for 35 d after weaning in pigs administered a single oral mega-dose of vitamin D 3 (40,000 IU) at birth (0.38 kg/d) compared with control pigs (0.41 kg/d).…”
Section: Discussionsupporting
confidence: 94%
“…3, the water supplementation of vitamin D 3 and E increased plasma 25-OH D 3 and α-tocopherol concentrations which mean supplementation of vitamins via drinking water to nursery pigs is an effective method to enhance plasma status of vitamins. This result agreed with a previous study which reported the water supplementation of vitamin D 3 to nursery pigs from weaning for 10 d elevated serum 25-OH D 3 concentration on d 10 postweaning (Flohr et al, 2014a). For vitamin E status, Wilburn et al (2008) reported the water vitamin E supplementation increased plasma α-tocopherol concentration of weanling pigs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations